Comparação do teste de Weil Felix com as provas de reação de imunofluorescência indireta e ensaio imunoenzimático como método de triagem para febre maculosa - Simone Berger Calic (1996)
671 samples of human serum were received by Fundação Ezequiel Dias (FUNED) from August 1993 to October 1995 provided from cities of Minas Gerais State, Brazil, with clinical suspected of Rocky Mountain Spotted Fever (FM) occurrence, Sera were assayed by Weil Felix (WF) agglutination test for FM screening and the results were compared to indirect immunofluorescence (IFA) and enzyme linked immunosorbent assay (ELISA). Results obtained showed high levels of specihcity from 85% to 96% and relative sensibility from 50% to 59%, Statistical analyses revealed chi square highest than critical value (10,38) p < 0,001 demonstrating an association among the tests when compared WF, IFA and ELISA. Results suggested that WF test is useful to screening FM.